2008
DOI: 10.1073/pnas.0808616105
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-mediated self-renewal of neural stem/progenitor cells

Abstract: In this work we have uncovered a role for Wnt signaling as an important regulator of stem cell self-renewal in the developing brain. We identified Wnt-responsive cells in the subventricular zone of the developing E14.5 mouse brain. Responding cell populations were enriched for self-renewing stem cells in primary culture, suggesting that Wnt signaling is a hallmark of self-renewing activity in vivo. We also tested whether Wnt signals directly influence neural stem cells. Using inhibitors of the Wnt pathway, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
246
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(253 citation statements)
references
References 23 publications
7
246
0
Order By: Relevance
“…Induced proliferation of hESCs/mNSCs [65,66] Recombinant Wnt-3a Induced proliferation and differentiation of hESCs [67] Wnt-4 silencing Impaired early differentiation in hECCs [68] Wnt-5a KO Impaired neurite development in the olfactory bulb (OB) [44] Wnt-1 and Wnt-5a DKO Impaired neurogenesis of midbrain dopaminergic neurons [52] Wnt-5a KO Impaired axon growth and guidance of dopaminergic neurons [45] Wnt-5a CM Increased synaptogenesis and maturation of hippocampal progenitors [69,70] Wnt-5a overexpression Induced axonal differentiation in hippocampal cultures [71] Wnt-7a KO Delayed morphological maturation of glomerular rosettes and synapsin I accumulation [46] Wnt-7a KO Impaired ventral midbrain neurogenesis [47] Wnt-7a and Dvl DKO Defective spine morphogenesis and mossy fiber-CA3 synaptic transmission [48] Wnt-7a Proposed as a key element in the regulation of NSC self-renewal/differentiation; altered spindle- Canonical Wnt receptors are also important for correct neural development (Table 2): FZD3 KO mice show impaired axonal guidance [73] while LRP6 KO mice present cortical defects [74]. Also, FZD1 has been shown to be the receptor for canonical Wnt-1 in mouse tyrosine hydroxylase positive neurons, which activates β-catenin-dependent signaling promoting neuroprotection in dopaminergic neurons [75].…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
“…Induced proliferation of hESCs/mNSCs [65,66] Recombinant Wnt-3a Induced proliferation and differentiation of hESCs [67] Wnt-4 silencing Impaired early differentiation in hECCs [68] Wnt-5a KO Impaired neurite development in the olfactory bulb (OB) [44] Wnt-1 and Wnt-5a DKO Impaired neurogenesis of midbrain dopaminergic neurons [52] Wnt-5a KO Impaired axon growth and guidance of dopaminergic neurons [45] Wnt-5a CM Increased synaptogenesis and maturation of hippocampal progenitors [69,70] Wnt-5a overexpression Induced axonal differentiation in hippocampal cultures [71] Wnt-7a KO Delayed morphological maturation of glomerular rosettes and synapsin I accumulation [46] Wnt-7a KO Impaired ventral midbrain neurogenesis [47] Wnt-7a and Dvl DKO Defective spine morphogenesis and mossy fiber-CA3 synaptic transmission [48] Wnt-7a Proposed as a key element in the regulation of NSC self-renewal/differentiation; altered spindle- Canonical Wnt receptors are also important for correct neural development (Table 2): FZD3 KO mice show impaired axonal guidance [73] while LRP6 KO mice present cortical defects [74]. Also, FZD1 has been shown to be the receptor for canonical Wnt-1 in mouse tyrosine hydroxylase positive neurons, which activates β-catenin-dependent signaling promoting neuroprotection in dopaminergic neurons [75].…”
Section: Neural Phenotype In Mammalian Models Referencementioning
confidence: 99%
“…Wnt-β-catenin signaling has clearly defined roles in both normal stem cells and cancer stem cells (Grigoryan et al, 2008). In brain, the Wnt signaling pathway regulates brain development as well as proliferation and selfrenewal of neural stem or progenitor cells in the fetal ventricular zone, the postnatal subventricular zone and hippocampus (McMahon et al, 1990;Thomas et al, 1990;Lie et al, 2005;Adachi et al, 2007;Kalani et al, 2008). The alterations of Wnt signaling pathway have been linked to medulloblastoma (Koch et al, 2001;Yokota et al, 2002).…”
Section: Wnt-β-catenin Signalingmentioning
confidence: 99%
“…This observation and the finding that all neurospheres that formed were strongly β-gal-positive, despite their original level of Axin2-lacZ expression, is an indication that the canonical Wnt signaling pathway is active and turned on during CN progenitor cell proliferation. Wnt-signaling has been put forward as a potent extracellular signal implicated in controlling different types of stem/progenitor cells (23,24,26), and we found that Axin2-lacZ-driven β-gal reporter gene expression was readily detectable in a subset of CN cells. Albeit circumstantial, this observation indicates that Wnt/β-catenin signaling might play a role in maintaining a transient niche for neural progenitor cells in the neonatal CN.…”
Section: Discussionmentioning
confidence: 84%
“…The canonical Wnt signaling pathway has been implicated in maintaining stem cell features in embryonic, neural, and nonneural stem cell populations (23)(24)(25)(26). We used heterozygous Axin2-lacZ reporter mice to visualize cells in the CN that display active Wnt/β-catenin signaling, indicated by β-galactosidase (β-gal) expression, driven by an Axin2 promoter (27,28).…”
Section: A Subpopulation Of Cn Cells Display Active Wnt/β-catenin Sigmentioning
confidence: 99%